2018
DOI: 10.1111/1759-7714.12801
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography‐guided hook wire localization facilitates video‐assisted thoracoscopic surgery of pulmonary ground‐glass nodules

Abstract: BackgroundThis retrospectively study was conducted to assess the efficiency and safety of computed tomography (CT)‐guided hook wire localization of pulmonary ground‐glass nodules (GGNs) prior to video‐assisted thoracoscopic surgery (VATS).MethodsFrom 2015 to 2018, a total of 86 patients with 86 pulmonary GGNs underwent preoperative CT‐guided hook wire localization before VATS. The technical details and clinicopathological findings were analyzed.ResultsAll 86 pulmonary GGNs (25 pure GGNs and 61 part‐solid GGNs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Most sub‐solid lung nodules tend to correspond to early‐stage lung cancer or precancerous lesions . Surgical resection may provide nearly 100% disease‐free survival for patients with sub‐solid lung nodules . Although the Fleischner Society has provided a detailed follow‐up protocol for sub‐solid lung nodules, this process can be mentally distressing for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most sub‐solid lung nodules tend to correspond to early‐stage lung cancer or precancerous lesions . Surgical resection may provide nearly 100% disease‐free survival for patients with sub‐solid lung nodules . Although the Fleischner Society has provided a detailed follow‐up protocol for sub‐solid lung nodules, this process can be mentally distressing for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Klinkenberg et al reported one case (0.7%) and Chen et al reported two cases (4.9%) of dislodgement in their studies As discussed in our former study, many effective measures are taken to prevent dislodgement . In terms of other complications, pneumothorax is the most common, with a reported incidence of 7.5–40% .…”
Section: Discussionmentioning
confidence: 54%
“…10,19 As discussed in our former study, many effective measures are taken to prevent dislodgement. 11 In terms of other complications, pneumothorax is the most common, 20 with a reported incidence of 7.5-40%. 15 In our cohort, asymptomatic minimal pneumothorax in 24 patients (27.3%) did not require further intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations